Variation in the pollen diet of managed bee species across European agroecosystems - Clément Tourbez; Antoine Gekière; Irene Bottero; Marie-Pierre Chauzat; Elena Cini; Francesca Corvucci; Joachim R. de Miranda; Gennaro Di Prisco; Christophe Dominik; Francesca V. Grillenzoni; Simon Hodge; Tomasz Kiljanek; et al. (Agriculture, Ecosystems & Environment, 2025)

What’s in the bee nest holes? A single aggregation of Megachile parietina reveals and helps to fill up Eltonian shortfalls - Elisa Monterastelli; Alfonso Orlotti; Giulia Calderai; Chiara Natali; Marta Mariotti Lippi; Claudio Ciofi; Alessandro Cini; Leonardo Dapporto; Marino Quaranta; Francesca Romana Dani (Journal of Insect Conservation, 2024)
Megachile (Chalicodoma) parietina (Geoffroy, 1785) is a Palearctic solitary bee included in the Red List of some central European Countries. Females build durable nests, reused year after year, by mixing soil with a salivary secretion. Like for most solitary bees, the resources contained within M. parietina nests attract several other insects which exploit pollen supplies or feed on the immature brood. These associated insects have mainly been studied for mantained bees and considered for their effect on the host reproductive success. A very large nesting aggregation of M. parietina in Central Tuscany has been studied for three consecutive years. We have identified 32 associated insect species, which certainly are an underestimate of the species present. Among the identified species, only eight had been previously reported for M. parietina . All the species were classified both according to the specificity for the host taxon ( Chalicodoma , Megachilidae, Anthophila, Hymenoptera, Others) and to the ecological relationship (cleptoparasites, parasitoids, predators of larvae, food commensal, scavengers, and occasional nest users). This highlighted both the richness of the ecological network within the nesting aggregation and the value of studying these nesting sites to fill Eltonian shortfalls, i.e. the deficiency in ecology knowledge, of bees and their associated fauna. Implications for insect conservation. We suggest that, besides their role in pollination, large and stable bee nesting sites increase the local insect biodiversity, and that attention should be paid to their conservation within actions aimed to support populations of wild pollinators.

A holistic approach to food loss reduction in Africa: food loss analysis, integrated capacity development and policy implications - Mireille Totobesola; Robert Delve; Jean d’Amour Nkundimana; Leonardo Cini; Francesca Gianfelici; Brighton Mvumi; Silvia Gaiani; Alessandra Pani; Alejandra Safa Barraza; Rosa S. Rolle (Food Security, 2022)
Food insecurity in the African context is a critical issue; yet total food losses are estimated at 15.9% and 17.2% in quantity and in caloric value, respectively (FAO, 2019). Currently across the continent, there is insufficient funding and the lack of policy mechanisms to support interdisciplinary analytical approaches and data collection systems to better inform the reduction of food loss. This paper highlights the critical need for a paradigm shift of current research and development programs aimed at food loss reduction, as demonstrated by findings of a project implemented in Burkina Faso, the Democratic Republic of Congo and Uganda by the United Nations Rome-based Agencies (RBAs) – The Food and Agriculture Organization of the United Nations (FAO), the International Fund for Agricultural Development (IFAD) and the World Food Programme (WFP). Quantitative and qualitative food loss data generated by applying the FAO Food Loss Analysis (FLA) methodology to identify critical loss points in the supply chains of nationally prioritized staple food crops, informed the development of practical knowledge-sharing tools and policy guidelines on food loss reduction and contributed to the development of a comprehensive approach for mainstreaming food loss reduction strategies and solutions into national strategic frameworks. Furthermore, a holistic approach that integrates multi-stakeholder engagement, and evidence generation through the implementation of pilot activities to shape local and regional policies and strategies proved essential to the realization of beneficial outcomes in the respective countries. The project also recognized the critical importance of integrating gender considerations and particularly the inclusion of women in harvest and post-harvest operations and in decision-making. All of these outcomes have contributed to the advancement of knowledge and strategic approaches toward reducing postharvest loss, achieving SDG target 12.3 and meeting the targets set by the Malabo Declaration. In short, the project effectively translated commitment into action in all three beneficiary countries.

Humans adjust their grip force when passing an object according to the observed speed of the partner’s reaching out movement - Marco Controzzi; Harmeet Singh; Francesca Cini; Torquato Cecchini; Alan Wing; Christian Cipriani (Experimental Brain Research, 2018)